Pawang Hujan Phenomena in the Perspective of Islamic Education in Nagari Sikucua East, Padang Pariaman District - Raihan, Mohammad; Rivauzi, Ahmad (EDUMALSYS Journal of Research in Education Management, 2023)
This study aims to find out how the perspective of Islamic education in viewing the rain charmer phenomenon. Researchers used qualitative methods with a qualitative descriptive approach. The informants in this study were 15 people consisting of Wali Nagari Sikucua Timur, Pawang Rain, Community Leaders, Traditional Leaders, Religious Leaders, Bundo Kanduang, and the Matua Koto Hilalang Nagari Sikucua Timur Community, Padang Pariaman Regency, which the researchers selected using a purposive sampling technique. The data obtained will then be analyzed using data analysis techniques according to Miles and Huberman, namely reducing data, displaying data, and drawing conclusions from the data. The results of this study prove that the profession of rain handler in Nagari Sikucua Timur, Padang Pariaman Regency teaches us to keep asking God as well as teaches us to help others without expecting anything in return and teaches us to be trustworthy in the work that has been entrusted. If you look at the substance of the implementation using the recitation of bismillah, sholawat, and dhikr, this aims to propagate Islamic symbols.